THE EFFECT OF ENVIRONMENT, SOCIAL AND GOVERNANCE ON FIRM VALUE WITH FIRM SIZE AS A MODERATING VARIABLE - Maria Gratia Kolo; Muslichah Muslichah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study examines the effect of Environment, Social, and Governance (ESG) factors on firm value, with company size as a moderating variable, in basic materials and industrials companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023.  Fourteen companies were picked using purposive sampling, resulting in a total of 42 observations.  Data were examined utilizing multiple regression and moderated regression analysis (MRA) with SPSS 26. The results demonstrate that ESG as a whole and the environmental component do not substantially affect corporate value; however, the social and governance facets have an effect on firm value. Furthermore, firm size does moderate the influence of ESG and environmental issues on firm value; instead, it moderates the impact of social and governance elements on firm value.